Effects of “sargaço” extraction residues on seed germination - Tiago Sousa (Instituto Politécnico de Viseu, 2020)
Introduction: The “Sargaço” is a mixture of seaweeds that grow on the rocks of the Minho coast and the seaweeds during their development synthesize different metabolites. During the seaweed extraction process, some of these metabolites are not taken, thus not promoting the circular economy.